Metabolites of endophytic fungi isolated from leaves of Bauhinia variegata exhibit antioxidant activity and agonist activity on peroxisome proliferator-activated receptors α, β/δ and γ - Mesquita, Pedro Góes; Araujo, Laiza Magalhaes de; Neves, Francisco de Assis Rocha; Borin, Maria de Fátima (Frontiers in Fungal Biology, 2022)
Diabetes mellitus is a metabolic disorder that affects millions of people worldwide and is linked to oxidative stress and inflammation. Thiazolidinediones (TZD) improve insulin sensitization and glucose homeostasis mediated by the activation of peroxisome proliferator-activated receptors gamma (PPARgamma) in patients with type 2 diabetes. However, their use is associated with severe adverse effects such as loss of bone mass, retention of body fluids, liver and heart problems, and increased risk of bladder cancer. Partial PPARgammaagonists can promote the beneficial effects of thiazolidinediones with fewer adverse effects. Endophytic fungi colonize plant tissues and have a particularly active metabolism caused by the interaction with them, which leads to the production of natural products with significant biological effects that may be like that of the colonized plant. Here, we identify seven endophytic fungi isolated from Bauhinia variegata leaves that have antioxidant activities. Also, one of the extracts presented pan-agonist activity on PPAR, and another showed activity in PPARalphaand PPARbeta/delta. A better understanding of this relationship could help to comprehend the mechanism of action of antioxidants in treating diabetes and its complications. Moreover, compounds with these capabilities to reduce oxidative stress and activate the receptor that promotes glucose homeostasis are promising candidates in treatment of diabetes.